2017
DOI: 10.1002/path.4892
|View full text |Cite
|
Sign up to set email alerts
|

High expression of insulin receptor on tumour‐associated blood vessels in invasive bladder cancer predicts poor overall and progression‐free survival

Abstract: Bladder cancer is a frequently recurring disease with a very poor prognosis once progressed to invasive stages, and tumour-associated blood vessels play a crucial role in this process. In order to identify novel biomarkers associated with progression, we isolated blood vascular endothelial cells (BECs) from human invasive bladder cancers and matched normal bladder tissue, and found that tumour-associated BECs greatly up-regulated the expression of insulin receptor (INSR). High expression of INSR on BECs of inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 59 publications
2
24
0
Order By: Relevance
“…One study has shown that high BMI in conjunction with negative expression of progesterone receptors serves as an independent risk factor for breast cancer recurrences in patients treated with adjuvant aromatase inhibitors (40). In muscle-invasive bladder cancer, expression of insulin receptors in tumor-associated blood vessels also has correlated with poor overall and progression-free survival (41). Consequently, assay of plasma obesity-related molecules or evaluation of hormonal receptor expression in bladder tumors may help elucidate the mechanism of tumorigenesis encouraged by higher BMI in patients with bladder cancer.…”
Section: Discussionmentioning
confidence: 99%
“…One study has shown that high BMI in conjunction with negative expression of progesterone receptors serves as an independent risk factor for breast cancer recurrences in patients treated with adjuvant aromatase inhibitors (40). In muscle-invasive bladder cancer, expression of insulin receptors in tumor-associated blood vessels also has correlated with poor overall and progression-free survival (41). Consequently, assay of plasma obesity-related molecules or evaluation of hormonal receptor expression in bladder tumors may help elucidate the mechanism of tumorigenesis encouraged by higher BMI in patients with bladder cancer.…”
Section: Discussionmentioning
confidence: 99%
“…To explore the effects of AKT2 dysregulation on endothelial cells, we utilized previously engineered human pluripotent stem cell (hPSC) HUES9 cell lines carrying AKT2 KO and AKT2 E17K mutations [4], along with the corresponding WT cell line, and differentiated each into ECs using a previously published protocol [7,9]. These ECs were then subjected to both molecular profiling studies and functional assays ( Figure 1A).…”
Section: Resultsmentioning
confidence: 99%
“…ECs play a central role in the cardiovascular, renal, or neural complications of diabetes mellitus and metabolic syndrome [5]. ECs are an important target of insulin [6,7], and the primary effect of insulin is to activate the kinase AKT1, which then leads to phosphorylation of eNOS and vasodilatation to increase nutrient delivery to tissues [8]. The specific function of the closely related kinase AKT2 in endothelial cells has not been studied.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, we compared pathways predicted with annotations of these six RBPs in GeneCards 6 and found that HSPG2 acted as an anti-angiogenic and anti-tumor peptide that inhibited endothelial cell migration and collagen-induced endothelial tube morphogenesis. Angiogenesis is thought to be a critical procedure of promoting BLCA progression and associated with poor survival ( Bochner et al, 1995 ; Roudnicky et al, 2017 ). Among these prognostic RBPs, HSPG2 demonstrated an anti-angiogenesis effect via binding to α2β1 integrin and interacting with VEGFR2 at the surface of endothelial cells ( Woodall et al, 2008 ; Goyal et al, 2012 ; Poluzzi et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%